Aplicação de Isolamento Térmico pelo Exterior Tipo ETICS associado a Revestimento Cerâmico - Cristina da Conceição Brites de Moura (2012)
There has been a significant evolution in the way are executed the facades of buildings in Portugal. In the last decade, was introduced in Portugal the thermal insulation system from outside, ETICS, in order to respond to growing requirements for comfort hygrothermal. This system is a great solution, both from the point of view of energy as the constructive point of view. Portugal has also, a strong tradition with respect to the cladding with ceramic. In the construction Portuguese, the ceramic coatings glued still widely used, because they offer high durability, good technical performance and many aesthetic possibilities. Despite the evolution of the industry and methods of fixation, continues to be a coating often confronted with severe pathologies. The fact this type of cladding begun to emerge in recent years, with increasing frequency, applied to ETICS system, leads us to consider until point is feasible we can consider this system valid for creating an ETA. Thus was evaluated during this work the process for developing an ETA and their requirements. Proceeded to the characterization of the ceramic, the classification of joints, and the identification of the major pathologies associated with the system. After this analysis, picked up a sample of buildings, with the characteristics of the application system external thermal insulation type ETICS associated with ceramic coating, in order to achieve evaluate it on its performance. Thus this work aimed to make a sample of the works with this system and trying to understand through the same, the feasibility of the system. KEYWORDS: ETICS, CERAMICS, COLLAGE, FACADE, APPROVAL.